1997
DOI: 10.1002/(sici)1097-0142(19970701)80:1<91::aid-cncr12>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the uterine cervix

Abstract: The finding of EBV associations in cervical LELC supports the hypothesis that EBV may be involved in the pathogenesis of tumors that arise in the cervix. It is possible that cervical LELC may follow a different pathway in the pathogenesis of LELC in Asian women as compared with the more common forms of squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 22 publications
0
26
1
1
Order By: Relevance
“…Despite of the fact of a strong p16 positivity, immunohistochemistry of HPV was negative. There is some controversy about HPV related LELC [25,13,14], but a few reports give evidence for this possible pathogenesis in the uterine cervix [8,10]. Lichen sclerosus is a further precursor lesion of vulvar carcinoma, but we did not find lichenoid changes in the stromal compartments of the excision specimen.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Despite of the fact of a strong p16 positivity, immunohistochemistry of HPV was negative. There is some controversy about HPV related LELC [25,13,14], but a few reports give evidence for this possible pathogenesis in the uterine cervix [8,10]. Lichen sclerosus is a further precursor lesion of vulvar carcinoma, but we did not find lichenoid changes in the stromal compartments of the excision specimen.…”
Section: Discussioncontrasting
confidence: 53%
“…Whereas the neoplasms of the upper aerodigestive tract are EBV-related, the most cases of LELC described so far were EBV negative [8-11], especially those in the skin and extracervical gynaecological sites [20-23]. Only very few reports could figure out a correlation between EBV and LELC of the uterine cervix [13,14]. With a negative EBV in-situ hybridisation this pathway could be excluded for our patient.…”
Section: Discussionmentioning
confidence: 86%
“…Tseng et al [20] reported a high incidence of EBV in lymphoepithelial like-carcinoma (LELC) patients but did not show any association with HPV. These findings are in contradiction with what has been previously reported [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This virus infects B cells of the immune system and epithelial cells. There is evidence that infection with EBV is associated with a higher risk of particular forms of cancer and may function as an oncogenic agent (20). Thus, the association of EBV with premalignant changes, including those observed in the four patients of the current study, is worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%